Evaluating the Effectiveness of Neurofeedback Treatment on Depression, Anxiety, Stress and Abdominal Pain in Patients with Chronic Psychosomatic Abdominal Pains - Shafaei, Hassan (Pakistan Journal of Medical & Health Sciences, 2022)
The aim of this study was to evaluate the effectiveness of neurofeedback therapy on depression, anxiety and stress in female patients with chronic clinical psychosomatic abdominal pain in Tabriz. This quasi-experimental study is a pre-test-post-test with a control group. The statistical population of this study was all women with chronic psychosomatic abdominal pain, from which a sample of 40 people was selected, from which the study was performed with 30 people (15 in the experimental group and 15 in the control group). These individuals were randomly assigned to two groups of 15 in the experimental group and the control group. In this intervention method, the experimental group underwent neurofeedback treatment for 10 weeks (three sessions of 40 minutes per week) and the control group did not receive any intervention and was placed on a waiting list. The experimental and control groups also completed the Depression, Anxiety and Stress Questionnaire in the pre-test and post-test. Analysis of MANCOVA was used to analyze the data. The results of analysis of MANCOVA showed that neurofeedback treatment was effective in reducing anxiety and depression (P <0.001). In other words, 53% of the changes in depression and 57% of the changes in anxiety were due to neurofeedback; but neurofeedback had no effect on stress. Neurofeedback was able to reduce depression and anxiety in women with abdominal pain but had no effect on their stress level.